Literature Review of Artificial Intelligence in Learning: Trends and Opportunities - Duwi Purnama Sidik; Abdullah Rozak; Fatqurhohman Fatqurhohman; Henri Fatkurochman (Ihsan Cahaya Pustaka, 2025)
Artificial intelligence (AI) is reshaping education by enabling adaptive, personalized, and efficient learning experiences. This literature review examines the current trends, opportunities, and challenges of AI in education, with a focus on Intelligent Tutoring Systems, automated grading, and personalized learning platforms. Evidence suggests that AI can significantly enhance student engagement, learning outcomes, and instructional efficiency by tailoring content and feedback to individual needs. At the same time, ethical considerations such as data privacy, algorithmic bias, and transparency remain critical challenges. Integrating AI into curriculum design and educator professional development is essential to maximize its benefits while promoting responsible and equitable use. By synthesizing recent research across multiple educational contexts, this review offers insights for researchers, educators, and policymakers to strategically implement AI technologies. The findings underscore that AI, when thoughtfully applied, can complement human intelligence, foster innovative pedagogical practices, and create more engaging, inclusive, and future-ready learning environments.